Problematika Mahasiswa Pendidikan Bahasa Jerman Yang Belum Pernah Mendapatkan Pelajaran bahasa Jerman di Jenjang Pendidikan Sebelumnya - Ihsan, Ihsan; Al-Ilmul, Syarifah Fatimah (Interference: Journal of Language, Literature, and Linguistics, 2021)
This study is aimed at knowing the problematics of german education students who have never gotten german lessons in previous education levels. This study belongs to descriptive qualitative. The population in this study is German Education students of State University of Makassar, class of 2019. The samples in the study are students of the class of 2019 who have never learned German in previous education level. The data were collected from observation and questionnaires. The results of the study are problems faced in the learning process including internal factors and external factors. The internal factors are the ability to memorize teaching materials, explore memorized teaching materials, and learning habit. Whilst external factors are academic facilities and infrastructure, teaching staff assessment policies, and the social environment on campus. The main problems are: the lack of vocabulary, difficulties in sentences structure (grammar) and the lack of ability in pronunciation.